A cross sectional study on the prevalence of overweight and obesity in affluent school children of central Kerala - Viswambharan, Jaya Koothupalakkal; Abraham, Ruth (International Journal Of Community Medicine And Public Health, 2021)
Background: Childhood obesity is increasing in India in recent years. The recent economic development and nutritional transition has been attributed to the increase in childhood obesity. Obesity in childhood predisposes to many cardiovascular/endocrinal problems in later years of life. This problem is taking an epidemic lever in Kerala too. Objective was to assess the prevalence of obesity among affluent school children in Thrissur. Methods: This cross sectional study was conducted among 1104 private school children in Thrissur, Kerala, South India between November 2019 to October 2020. Prior permission to conduct the study was obtained from the respective authorities. Parent assent was obtained. A semi-structured questionnaire was used. Anthropometric measurements- height and weight were measured using the standard methods prescribed in the World Health Organization STEPwise approach to surveillance (WHO-STEPS) field manual.Bodymass index (BMI) was calculated and classified as per WHO guidelines for their respective ages. Results: 13.9% were overweight and 7.3% were obese. The combined prevalence of overweight and obesity was 21.2%. Prevalence of obesity and overweight was 23.7% among boys and 18.2% among girls. The prevalence of overweight and obesity increases with age. Conclusions: Appropriate preventive measures like change in food habits and life style practices, increasing physical activities, health education for parents and children, needs to be taken.